A Comparison of DSM-IV Versus DSM-5 Substance Use Disorder Diagnoses in Adolescent Populations. Issue 5 (2nd September 2016) - Malone, Marisa; Hoffmann, Norman
ABSTRACT: Most of the considerations for changes to the diagnostic criteria for substance use disorders have focused on adults. This study compares the diagnostic determinations for substance use disorders with the former Diagnostic and Statistical Manual of Mental Disorders ( DSM -IV-TR) versus the current DSM -5 diagnostic criteria among samples of adolescents likely to be evaluated. The DSM -5 has three classifications (mild, moderate, and severe) based on the number of positive findings for 11 diagnostic criteria as opposed to the abuse versus dependence distinction of the DSM -IV-TR. The new criteria replace the criterion of legal problems with one of craving and compulsion to use. The sample consists of 571 males and 333 females who are evaluated either in the juvenile justice system or upon presenting for an evaluation at addiction treatment programs. Results revealed that relatively few cases with no current diagnosis will receive a diagnosis with the new criteria. Similarly, more than 90% of those with a dependence diagnosis fall into the "severe" DSM -5 designation. The most variation will occur for those with a current diagnosis of abuse. Few individuals were "diagnostic orphans" having some dependence indications but no diagnosis with the DSM -IV-TR. Most of these cases do not receive a DSM -5 diagnosis. Results also show that the individual criterion vary widely in whether they indicate a serious condition.